Working with Less Water for Corn Production - A. Schlegel; F. Lamm; D. O'Brien (Kansas Agricultural Experiment Station Research Reports, 2021)
Research was conducted at Colby and Tribune, KS, from 2018–2020 to evaluate irrigation strategies, hybrid maturity, and seeding rate on corn production. Irrigation strategies were a combination of irrigation frequency/timing (weekly or bi-weekly) applied pre- and post-silking, and irrigation amounts (1 and 1.5 inch/week). Hybrid maturities were 108- and 111-day hybrids planted at 25,000 and 30,000 seeds/a. Average irrigation amounts ranged from 7.33 to 12.50 in. at Colby and 8.41 to 13.44 in. at Tribune. At Colby, average corn yields were not affected by irrigation strategies or seeding rate but were 8 bu/a greater with the 108-day hybrid. At Tribune, average corn yields were greater with weekly post-silking irrigation and with the higher seeding rate but not affected by hybrid maturity. The water limitations in this study are relatively severe and these results might not replicate under less stressful irrigation regimes.
Keywords: deficit irrigation; water productivity; irrigation scheduling